Dilatancy-triggering surface for advanced constitutive modeling of sand. Issue 2 (1st April 2019) - Woo, S. I.; Salgado, R.; Prezzi, M.
Abstract : This paper presents, for sand, a formulation for a surface in stress space defining the onset of dilatancy based on the volumetric threshold strain concept, the expression for the small-strain shear modulus in terms of soil state, and an expression for secant shear modulus degradation with increasing shear strain. The size of the surface depends on both density (void ratio) and mean effective stress. The use of the proposed surface is demonstrated for Toyoura sand. The paper also presents a multiaxial formulation for the surface that can include kinematic hardening. The proposed surface can be useful in constitutive modeling, especially to capture seismic or cyclic loading conditions.